FINANCIAL FEASIBILITY ANALYSIS AND PRODUCTIVITY ENHANCEMENT STRATEGIES FOR SMALLHOLDER OIL PALM PLANTATION IN MUARO JAMBI REGENCY TO SUPPORT SUSTAINABLE AGRIBUSINESS - Karina Rahmah; Ulidesi Siadari; Sri Utami Lestari; Vika Indah Rahayu; Dwi Arianti (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2026)
This study analyzes the financial feasibility of post-replanting smallholder oil palm farming and formulates priority strategies to enhance productivity in support of sustainable agribusiness development in Muaro Jambi Regency. Primary data were collected through structured interviews with 30 smallholder farmers in Sungai Bahar District who had participated in the Oil Palm Replanting (PSR) program. Financial feasibility was evaluated using Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period (PP), while strategic priorities were determined using a SWOT–QSPM approach. The results show that post-replanting oil palm farming is financially feasible, with an NPV of IDR 28,450,000 per hectare, an IRR of 18.2%. The payback period is estimated at 4.4 years, indicating a relatively fast return on investment under existing conditions. The average farmer income reaches IDR 68,326,560 per year. However, income constraints remain significant during the immature crop phase (TBM), which limits short-term cash flow. The QSPM analysis identifies institutional strengthening, intercropping-based diversification, and optimization of PSR support as priority strategies to enhance productivity and ensure long-term sustainability. These findings provide empirical evidence that integrating financial feasibility with strategic planning is essential for improving the resilience of smallholder oil palm agribusiness.